The exercise of friendship in the High Roman Empire - Wei, RJY (2009)
In the introduction, I discuss the problems scholars experience in trying to define the concept of Roman friendship. I argue that amicitia cannot be equated with patronage, and present justification based on some primary literature. Brief words are then offered on the sociology of friendship, and an attempt is made to relate ideas from modern sociology to ancient friendship.